Study of water degradation due to community activities in The Lake Batur ecosystem, Bangli District, Bali - Nuringtyas, Satria Bagus; Harini, Rika; Widayani, Prima (EDP Sciences, 2023)
Lake Batur is a aquatic ecosystem that has a role for domestic and economic needs of the people in Kintamani District, Bangli Regency even widely used within the Bali Province. This lake is one of the national priority that must be immediately saved due to degradation and sedimentation based on the stipulation in the Indonesian Presidential Regulation. This research aims to determine the level of water quality of Lake Batur, identify community activities and its correlation with water degradation, and formulate strategies for controlling water ecosystem. Primary data for this research are 11 different water sample points determined based on land use around the lake. The water sample datas then are tested in the laboratory to observe physical, chemical and biological parameters, then determine water quality index using NSF-WQI method and pollution index. Secondary data is interviews with communities around. Respondents were selected using purposive sampling classified based on the livelihoods of local residents. Based on calculations using the NSF-WQI method, Lake Batur water has a score of 68.97 or classified as moderate status. The water quality of Lake Batur calculated using polution index method has a score of 8.56, which is classified in the moderately polluted. Community activities are very dependent on the existence of lakes and are very close to water bodies. Waste generated from various activities has a risk of water degradation and sedimentation. Waste and sedimentation can occur due to the use of chemicals. Communities should switch for using organic materials such as compost for farmers and natural fish food for fish cultivators, as well as being orderly in implementing existing policies. The government needs to provide physical and non-physical facilities to support for reducing the risk of. Investors are expected to follow policies and apply ecotourism principles. © 2023 EDP Sciences. All rights reserved.